2019
DOI: 10.1186/s12985-019-1181-1
|View full text |Cite
|
Sign up to set email alerts
|

Caraway yellows virus, a novel nepovirus from Carum carvi

Abstract: A novel nepovirus was identified and characterised from caraway, and tentatively named caraway yellows virus (CawYV). Tubular structures with isomeric virus particles typical for nepoviruses were observed in infected tissues by electron microscopy. The whole genome of CawYV was identified by high throughput sequencing (HTS). It consists of two segments with 8026 nt for RNA1 and 6405 nt for RNA2, excluding the poly(A) tails. CawYV-RNA1 shared closest nt identity to peach rosette mosaic virus (PRMV) with 63%, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Two nepoviruses (GFLV and ArMV) made up the majority of sequences analyzed in this study, while most species were represented by one or a few sequences of either genomic RNAs (Table 1 ). Novel nepoviruses used in this study included MMLRaV [ 31 ], caraway yellows virus [ 12 ], potato virus B [ 4 ], and red clover nepovirus A [ 25 ]. A few new viruses and isolates belonging to the genus Nepovirus have been identified since we last consulted NCBI (January 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two nepoviruses (GFLV and ArMV) made up the majority of sequences analyzed in this study, while most species were represented by one or a few sequences of either genomic RNAs (Table 1 ). Novel nepoviruses used in this study included MMLRaV [ 31 ], caraway yellows virus [ 12 ], potato virus B [ 4 ], and red clover nepovirus A [ 25 ]. A few new viruses and isolates belonging to the genus Nepovirus have been identified since we last consulted NCBI (January 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, diversity studies and phylogenetic analysis have been reported for members of the family Secoviridae , including nepoviruses [ 45 , 51 ]. However, several new nepoviruses have been characterized recently, and the number of complete genome sequences of nepovirus isolates has increased exponentially in the past five years [ 1 , 2 , 4 , 12 , 15 , 18 , 23 25 , 41 , 50 , 55 , 56 , 58 ]. In this study, we built on these latest advancements in nepovirus research and carried out metagenomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…No prior knowledge about the pathogen is needed for HTS since all the nucleic acid (viral or non-viral) in the sample can be sequenced. Many previously undescribed viruses and viroids have been discovered using HTS and the number is constantly increasing [ 14 17 ]. However, HTS-based approaches for virus/viroid detection is facing several challenges in order to be validated for routine use diagnostic laboratories [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato black ring virus (TBRV), a typical member of Nepovirus genus within the Secoviridae family, infects a wide range of economically important plants worldwide, including tomato, strawberry, potato, celery, and artichoke 25 . Gaafar et al reported that a caraway yellows virus (CawYV) infection results in systemic yellowing in Caraway 26 . Grapevine fan leaf virus (GFLV), a picorna-like plant virus, is severely in responsible for a widespread disease in vineyards worldwide 27 .…”
Section: Discussionmentioning
confidence: 99%